2017
DOI: 10.1158/0008-5472.can-16-2704
|View full text |Cite
|
Sign up to set email alerts
|

Posttranscriptional Regulation of PARG mRNA by HuR Facilitates DNA Repair and Resistance to PARP Inhibitors

Abstract: The majority of pancreatic ductal adenocarcinomas (PDA) rely on the mRNA stability factor HuR (ELAV-L1) to drive cancer growth and progression. Here we show that CRISPR-Cas9-mediated silencing of the HuR locus increases the relative sensitivity of PDA cells to PARP inhibitors (PARPi). PDA cells treated with PARPi stimulated translocation of HuR from the nucleus to the cytoplasm, specifically promoting stabilization of a new target, polyADP-ribose glycohydrolase (PARG) mRNA, by binding a unique sequence embedde… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
65
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 64 publications
3
65
0
Order By: Relevance
“…In the process, HuR is thought to bind to target mRNA and then form an HuR‐mRNA complex in the nucleus, which is then exported to the cytoplasm to protect the bound mRNA from degradation. There is mounting experimental evidence suggesting that there is an increase in cytoplasmic HuR after stimulation, which is considered a crucial step in the increased stability of many HuR‐bound mRNAs . In accordance with this model, our immunofluorescent staining findings indicate that IL‐4 can also regulate HuR for nuclear shuttle.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In the process, HuR is thought to bind to target mRNA and then form an HuR‐mRNA complex in the nucleus, which is then exported to the cytoplasm to protect the bound mRNA from degradation. There is mounting experimental evidence suggesting that there is an increase in cytoplasmic HuR after stimulation, which is considered a crucial step in the increased stability of many HuR‐bound mRNAs . In accordance with this model, our immunofluorescent staining findings indicate that IL‐4 can also regulate HuR for nuclear shuttle.…”
Section: Discussionsupporting
confidence: 87%
“…The posttranscriptional events associated with adenylate‐ and uridylate‐rich elements (AREs)‒containing gene are recognized as important control points in gene regulation . The mechanisms of mRNA decay regulation are closely associated with specific target regions, including AREs in the 3' untranslated regions (3'UTRs) of mRNA .…”
mentioning
confidence: 99%
“…Furthermore, poly(ADP‐ribose) glycohydrolase (PARG), which hydrolyzes PAR moieties, harbors patient‐derived alterations of unknown relevance, which may impact PARP‐1 activation status by differentially regulating PAR levels. It has recently been reported that PARG impacts the response to PARPi in models of pancreatic cancer (Chand et al , ). Irrespective of the mechanism(s) by which PARP‐1 is hyperactivated in advanced PCa, studies described herein yield novel insights into the downstream functions of elevated PARP‐1 activity.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptome wide analysis of samples from cells exposed to IR radiation revealed a decrease in HuR binding to its target mRNAs due to activated CHK2‐mediated phosphorylation (Masuda et al, ). Upon genotoxic stress, HuR can be PARylated by poly(ADP‐ribose) polymerase 1 (PARP1) facilitating its cytoplasmic translocation and regulation of its binding to target mRNAs (Chand et al, ; Gagné et al, ; Y. Ke et al, ). dePARylation of HuR facilitates its release from target mRNAs and its shuttling back into the nucleus.…”
Section: Deadenylation: Rbps and Micrornasmentioning
confidence: 99%